Proportion of women on the editorial committees of dental journals in the world - Aquino Canchari, Christian Renzo; Ojeda-Gómez., Roberto; Merizalde Ortega, Nadia Inés; Rodríguez Valladares, Ana Katthia (Brazilian Dental Science, 2021)
Objective: Despite the increase in the female contribution to careers in the health sector, Dentistry has shown slow progress towards gender equality. The objective of this study was to quantify the proportion of women in the editorial committees of dental journals in the world. Material and Methods: Dental journals published in the world were compiled, which met inclusion criteria: dental journals indexed to Scopus in their 2020 edition, access to the composition of the editorial committee. Non-current journals, without access to their website, journals not classified in a quartile, and journals with publishers outside their country of origin, were excluded. The selection of journals was carried out from January 11 to 19, 2021. The analysis variables were the composition of the editorial committee, dental specialty according to the SJR category and the title of the journal, quartile of the journal, and country of origin of the editorial headquarters. Results: One hundred eighty nine journals were identified. Women represented 22.91% for the position of director or editor-in-chief. With respect to associate editors and members of the editorial board, 24.76% and 22.91% were women, respectively. Likewise, greater female participation was observed in Q2 and Q1 journals and in thematic areas of Geriatric Dentistry, Dental Education, Dental Public Health, and Basic Sciences. Conclusion: The findings demonstrate the low proportion of women on the editorial boards of dental journals in the world. KEYWORDS Gender; Women; Dentistry; Editor; Editorial board; Research.